BFA Show 2017 - Chitrakar, Madan (SIRJANĀ – A Journal Of Arts and Art Education, 2017)
The quality of artistic creation is a parameter of the quality that an art institution offers to its students. The students of Sirjana College of Fine Arts have set an exemplary benchmark of artistic talent through their amazing creations. The college had organised an art exhibition entitled - BFA SHOW 2017 from July 10 to 17 this year. The exhibition showcased the representative artworks of our final year Bachelor students in the academic year 2016/2017. SIRJANĀ takes a look on paintings, sculptures, graphic communication works and installations displayed during the BFA SHOW 2017.